Characterization of Active Compounds of Different Garlic (Allium sativum L.) Cultivars - Szychowski Konrad A.; Rybczyńska-Tkaczyk Kamila; Gaweł-Bęben Katarzyna; Świeca Michał; Karaś Monika; Jakubczyk Anna; Matysiak Magdalena; Binduga Urszula E.; Gmiński Jan (Polish Journal of Food and Nutrition Sciences)
Garlic (Allium sativum L.) has a reputation as a therapeutic agent for many different diseases such as microbial infections, hypertension, hypercholesterolaemia, diabetes, atherosclerosis and cancer. Health benefits of garlic depend on its content of biologically-active compounds, which differs between cultivars and geographical regions. The aim of this study was to evaluate and compare the biological activity of aqueous extracts from nine garlic varieties from different countries (Poland, Spain, China, Portugal, Burma, Thailand and Uzbekistan). Antioxidant properties were evaluated through free radical scavenging (DPPH•, ABTS•+) and ion chelation (Fe2+, Cu2+) activities. The cytotoxicity of garlic extracts was evaluated in vitro using Neutral Red Uptake assay in normal human skin fibroblasts. The obtained results revealed that garlic extracts contained the highest amount of syringic and p-hydroxybenzoic acids derivatives. The lowest IC50 values for DPPH•, ABTS•+ scavenging and Cu2+ chelating ability were determined in Chinese garlic extracts (4.63, 0.43 and 14.90 μg/mL, respectively). Extracts from Spanish cultivar Morado and Chinese garlic were highly cytotoxic to human skin fibroblasts as they reduced cellular proliferation by 70–90%. We showed diverse contents of proteins and phenolic components in garlic bulbs from different varieties. The obtained results could help to choose the cultivars of garlic which contain significant amounts of active compounds, have important antioxidant properties and display low antiproliferative effect and/or low cytotoxicity against normal human skin fibroblast BJ.